The Effect of Sales Promotion and Word of Mouth Towards Brand Image and Purchase Intention (Study Case of Sophie Paris in Pontianak) - Isnan, Raidita N. B1024131003 (Jurnal Manajemen Update, 2017)
The study investigated the effects of sales promotion, and word of mouth towards brand image and purchase intentions. Moreover, the direct and indirect effects of values and involvement on purchase intentions were studied. The study utilized the survey questionnaire and Sophie Paris product as the product being researched. The sample consisted of 100 respondent who responded to an anonymous questionnaire. Five hypotheses were tested and four of them were confirmed by the data. Using statistical software (SPSS) hypothesis shows that these variables have positive significant relationship. Practical contribution shows that this study can be used as a guideline to management and marketers to improve the product quality. The results of the study provide several theoretical and practical implications.Keywords: sales promotion, word of mouth, brand image, purchase intention, sophie paris.